Contactin-1/F3 Regulates Neuronal Migration and Morphogenesis Through Modulating RhoA Activity - Chen, Yi-An; Lu, I-Ling; Tsai, Jin-Wu (Frontiers in Molecular Neuroscience, 2018)
During neocortical development, newborn neurons migrate along radial fibers from the germinal ventricular zone (VZ) towards the cortical plate (CP) to populate the cerebral cortex. This radial migration requires adhesion activities between neurons and radial fibers; however, past research has identified only a limited number of adhesion molecules involved in this process. Contactin-1/F3 (Cntn1), a cell adhesion molecule expressed in the developing nervous system is essential for many key developmental events including neural cell adhesion, neurite outgrowth, axon guidance and myelination. However, the potential role of Cntn1 in neuronal migration during cortical development has not been investigated. Here we used in utero electroporation to introduce short hairpin RNA (shRNA) to knock down (KD) Cntn1 in neural stem cells in vivo. We found that Cntn1-KD led to a delay in neuronal migration. The arrested cells presented abnormal morphology in their leading process and more multipolar cells were observed in the deep layers of the brain, suggestive of dysregulation in process formation. Intriguingly, Cntn1-KD also resulted in upregulation of RhoA, a negative regulator for neuronal migration. Interference of RhoA by expression of the dominant-negative RhoAN19 partially rescued the neuronal migration defects caused by Cntn1 KD. Our results showed that Cntn1 is a novel adhesion protein that is essential for neuronal migration and regulates process formation of newborn cortical neurons through modulating RhoA signaling pathway.